Image analysis system for quantitative immunofluorescence measurement - Kolesnik, Yu. M.; Orlovsky, M. A.; Колесник, Юрій Михайлович (My University, 2002)
Immunofluorescence methods for hormonecontaining cells exposure are widely used but the quantitative nature of the immunostaining is frequently ignored. In this study, quantitative measurements of fluorescent pancreatic beta-cells before and after glucose stimulation were used to determine parameters characterizing insulin synthesis and secretory activity. Beta-cells in Wistar rats pancreatic islets were stained using indirect immunohistochemistry, with subsequent processing on image analysis systems. The presence of three independent beta-cell classes with different insulin synthesis and secretion activity was shown by subsequent cluster analysis and confirmed by changes in insulin blood level.
Keywords: insulin; beta-cells; immunofluorescence microscopy; image analysis